Characterization of the multidrug efflux regulator AcrR from Escherichia coli - Su, Chih-Chia (2007)
The Escherichia coli AcrR represses transcription of the acrB gene, which encodes the multidrug efflux pump AcrB that extrudes a wide variety of toxic compounds, by binding its target operator DNA. Fluorescence polarization was performed using purified, recombinant AcrR that contains a 6xHis tag at the C-terminus and a fluorescein-labeled 28-base pair oligonucleotide bearing a predicted palindrome (IR) operator sequence. Binding of AcrR to the predicted IR sequence occurred with a dissociation constant (K(D)) in the nanomolar range. Fluorescence polarization assays were also applied to characterize the affinity and specificity of AcrR interaction with three different fluorescent ligands, rhodamine 6G, ethidium and proflavin. The K(D) values for these ligands range from 4.2 to 10.1 μM, suggesting that AcrR is capable of recognizing a wide range of structurally dissimilar toxic compounds as it is in the case of the AcrB multidrug efflux pump. We found that the binding of rhodamine 6G to AcrR is inhibited by the presence of ethidium. In contrast, the dissociation constant of proflavin binding to AcrR was not affected by ethidium, a result suggesting that ethidium and proflavin are bound to distinct binding sites.